Directed genomic integration in Actinobacillus actinomycetemcomitans: generation of defined leukotoxin-negative mutants. - Kolodrubetz, D (1995)
To develop targeted gene integration in the periodontal pathogen Actinobacillus actinomycetemcomitans, a ColE1-based, spectinomycin-resistant plasmid containing a segment of the leukotoxin gene was electroporated into strain JP2. In all of the stable spectinomycin-resistant transformants that arose, the plasmid had recombined into the genomic leukotoxin locus since ColE1-based vectors cannot replicate extrachromosomally in A. actinomycetemcomitans. Directed genomic integration was then used to construct a leukotoxin-negative strain by transforming the leukotoxin-producing strain JP2 with a ColE1-based plasmid containing an internal fragment of the leukotoxin gene. Cytotoxicity assays proved that these transformants had < 0.1% of the leukotoxin activity of the parental strain. These results demonstrate that integration-based approaches can be used for generating isogenic mutants in specific virulence genes in A. actinomycetemcomitans.